1996
DOI: 10.1152/jn.1996.76.3.1367
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization of thalamocortical relays

Abstract: The thalamus has long been seen as responsible for relaying information on the way to the cerebral cortex, but it has not been until the last decade or so that the functional nature of this relay has attracted significant attention. Whereas earlier views tended to relegate thalamic function to a simple, machine-like relay process, recent research, reviewed in this article, demonstrates complicated circuitry and a rich array of membrane properties underlying the thalamic relay. It is now clear that the thalamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
543
0
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 711 publications
(565 citation statements)
references
References 195 publications
18
543
0
4
Order By: Relevance
“…These connections, however, are bidirectional (Erickson and Lewis, 2004;McFarland and Haber, 2002;Zikopoulos and Barbas, 2007). Moreover, while cortico-thalamic projections of the specific thalamic relay nuclei follow a general rule of reciprocity, the cortical projections to these thalamic nuclei are more extensive than their projections back to cortex (as seen in other thalamocortical systems) (Darian-Smith et al, 1999;McFarland and Haber, 2002;Sherman and Guillery, 1996). Importantly, in addition to the reciprocal connection, there is a nonreciprocal cortico-thalamic component.…”
Section: Thalamusmentioning
confidence: 99%
“…These connections, however, are bidirectional (Erickson and Lewis, 2004;McFarland and Haber, 2002;Zikopoulos and Barbas, 2007). Moreover, while cortico-thalamic projections of the specific thalamic relay nuclei follow a general rule of reciprocity, the cortical projections to these thalamic nuclei are more extensive than their projections back to cortex (as seen in other thalamocortical systems) (Darian-Smith et al, 1999;McFarland and Haber, 2002;Sherman and Guillery, 1996). Importantly, in addition to the reciprocal connection, there is a nonreciprocal cortico-thalamic component.…”
Section: Thalamusmentioning
confidence: 99%
“…If visual TRN neurons project back to the LGN neurons from which they receive their inputs (to the neurons representing the same part of the visual field), they would form "closed loop" connections, resulting in feedback inhibition. It has been suggested that during wakefulness, feedback inhibition initiates a rhythmic burst firing in LGN relay neurons, which may serve to alert visual cortex of behaviorally relevant sensory input (Crick, 1984;Sherman and Guillery, 1996) and facilitate signal transmission during visual target acquisition and early phases of fixation (Guido and Weyand, 1995; also see Ramcharan et al, 2000). The predominant increase in visual TRN activity that we have shown would be consistent with this view, because this increase in activity would be passed to the LGN as an increase in inhibition, resulting in the hyperpolarization of the LGN membrane and the consequent switching of these visual thalamic relay neurons from tonic to burst mode (Llinas and Jahnsen, 1982;Jahnsen and Llinas, 1984a,b;Sherman and Koch, 1986).…”
Section: Trn Modulation With Attentionmentioning
confidence: 99%
“…First, by feedback inhibition, they can control the cell's excitability. Second, by lateral inhibition, they can control the cell's receptive field properties (for reviews, see Pinault 2004;Sherman and Guillery 1996).…”
Section: Impact Of Trn Activity On the Receptive Fields Of Mg Cellsmentioning
confidence: 99%